2022
DOI: 10.1007/s40521-022-00326-1
|View full text |Cite
|
Sign up to set email alerts
|

New Biomarkers in Anaphylaxis (Beyond Tryptase)

Abstract: Purpose of Review The purpose of this review is to provide a better understanding of anaphylaxis pathophysiology and describe the underlying mechanisms, effector cells, and the potential biomarkers involved depending on the anaphylaxis endotypes. Recent Findings New insight into the potential relevance of pathways others than IgE-dependent anaphylaxis has been unraveled, as well as other biomarkers than tryptase, such as the role of platelet activation factor, basogranu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…It was previously demonstrated that C4a levels in ME/CFS patients were in general lower than in healthy control participants but elevated after exercise challenge and correlating with PEMassociated symptoms [34][35][36]. Interestingly, the rise in C4a levels was not observable one hour after being physically challenged [34][35][36] but only after six hours [36] and returned almost to baseline 24 hours post exercise. This suggests C4a as a potential PEM-associated biomarker and a pathophysiological marker in ME/CFS.…”
Section: Discussionmentioning
confidence: 89%
“…It was previously demonstrated that C4a levels in ME/CFS patients were in general lower than in healthy control participants but elevated after exercise challenge and correlating with PEMassociated symptoms [34][35][36]. Interestingly, the rise in C4a levels was not observable one hour after being physically challenged [34][35][36] but only after six hours [36] and returned almost to baseline 24 hours post exercise. This suggests C4a as a potential PEM-associated biomarker and a pathophysiological marker in ME/CFS.…”
Section: Discussionmentioning
confidence: 89%
“…As chronic mast cell activation is difficult to determine, due to the acute nature and short half-life of the major mediators tryptase and histamine [ 24 ], we aimed to measure the serum levels of ECP and EDN. The measurement of ECP did not reveal differences between the test groups of the study cohort and thus is not shown.…”
Section: Resultsmentioning
confidence: 99%
“…This is especially true for patients with food-induced anaphylaxis [31,32], in which only a 30% increase in tryptase seems to suffice [33]. It is possible that other mediators such as platelet-activating factor (PAF), prostaglandin D2, leukotriene E4, histamine, or other cytokines might be more sensitive in these patients [34][35][36][37]. Note that even when MCA is depicted, no conclusion can be drawn about the mechanism (IgE-mediated or non-IgE-mediated) responsible for MC degranulation [38,39].…”
Section: Discussionmentioning
confidence: 99%